Facilities management multiple criteria analysis/Pastatų ūkio valdymo daugiakriterinė analizė - Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras; Lepkova, Natalija; Zalatorius, Juozas (Journal of Civil Engineering and Management, 2001)
There are many definitions of facilities management. Wes McGregor and Danny Shiem-Shim Then describe facilities management (FM) as „the infrastructure that supports the people in the organization in their endeavours to achieve business goals”. In other words, facilities are the tools which people in the business have at their disposal to carry out their tasks. The Library of Congress (USA) provides an initial definition that is often quoted to explain the breadth of the field of facilities management: “The practice of coordinating the physical workplace with the people and work of the organization; integrates the principles of business administration, architecture and the behavioural and engineering sciences”. One of the most exact definitions of Facility Management used by F. Becker is: “Facility Management is a term which encompass the activities in planning, designing and managing complex facilities such as offices, hospitals and schools, differ from architecture and interior design”. The scope of the discipline covers all aspects of property, space, environmental control, health and safety, and support services, and requires that appropriate control point are established in the organization. The article presents an example of multiple criteria analysis of commerce centre in Vilnius. Initial data are given in Tables 1 and 2. A comparison of premises lease alternatives is carried out: from the tenant point of view and from that of the owner. The result—the best variant for tenants and owner is to rent the premises with all services. Article in Lithuanian. First Published Online: 30 Jul 2012